ETHNO-POLITICAL DISCOURSE OF INTER-ETHNIC IN-TERACTION IN INTERPRETING OF UKRAINIAN AND RUSSIAN SCIENTISTS: COMMON REVIEW - Гон, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article determines the main research vectors that formed in Russian and Ukrainian ethno-political science in the end of 1980th – in the first half of 1990th. The author interprets this period like that, when was beginning of ethno-political science in two sovereign states, identifies main thematic areas of research, which were formed in that time, gives some works that have appeared in the two countries over the period.